Geriatric Assessments Can Predict Functional Outcome and Mortality after Urological Tumor Surgery - Kahlmeyer, Andreas; Fiebig, Christian; Müller, Marco; Kraulich, Matthias; Brendel-Suchanek, Jonas; Kunath, Frank; Wach, Sven; Goebell, Peter; Ritt, Martin; Gaßmann, Karl-Günter; Wullich, Bernd (Urologia Internationalis, 2021)
Introduction: Older patients undergoing major urological tumor surgery are at severe risk of functional deterioration, complications, and mortality. We prospectively evaluated geriatric assessment tools and developed a novel easy-to-use assessment tool for clinical use. Methods: In 159 patients, geriatric assessment tools were used prior to cystectomy, prostatectomy, and renal tumor surgery, and their peri- and postoperative courses were recorded. Using all the tests, a short and easy-to-use assessment tool was developed, and nomograms were generated to predict functional outcomes and mortality. Results: Of all the patients, 13.8% underwent radical cystectomy, 37.7% underwent radical prostatectomy, and 48.4% underwent tumor surgery of the kidney at the age of 70 years or older. The average age was 75.6 years. Incomplete functional recovery at day 30 and day 180 was observed in 37.7% and 36.1% of the patients, respectively, and incomplete functional recovery was associated with impaired mobility, previous care dependency, frailty, comorbidities, and a high ASA score. The only predictor for high-grade complications was comorbidities, whereas mortality was associated with the geriatric screening tool scores, impaired mobility, preoperative care dependency, and comorbidities. The Erlangen Index (EI), a combination of the selected assessment tools, showed a good prediction of early (p = 0.002) and medium-term (p = 0.002) functional outcomes and mortality (p = 0.001). Conclusion: Our prospective evaluation confirms the high risk of incomplete functional recovery, high-grade complications, and mortality in older patients undergoing major urological tumor surgery. The EI is an easy-to-use preoperative assessment tool and therefore should be used in preoperative patient counseling.
CRIS-Team WoS Importer:2021-10-01